2015
DOI: 10.1124/dmd.115.065839
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Profiling and Distribution of Known and Novel Phase I and Phase II Metabolites of Efavirenz in Plasma, Urine, and Cerebrospinal Fluid

Abstract: Efavirenz (EFV) is principally metabolized by CYP2B6 to 8-hydroxyefavirenz (8OH-EFV) and to a lesser extent by CYP2A6 to 7-hydroxyefavirenz (7OH-EFV). So far, most metabolite profile analyses have been restricted to 8OH-EFV, 7OH-EFV, and EFV-N-glucuronide, even though these metabolites represent a minor percentage of EFV metabolites present in vivo. We have performed a quantitative phase I and II metabolite profile analysis by tandem mass spectrometry of plasma, cerebrospinal fluid (CSF), and urine samples in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…In vivo studies of efavirenz metabolism have largely reflected in vitro drug metabolism studies, which show that the primary route of efavirenz elimination is through CYP2B6-mediated hydroxylation (18)(19)(20). Of the genetically polymorphic CYPs evaluated in this study, only CYP2B6 metabolizer status was found to be a significant predictor of CL/F.…”
Section: Discussionmentioning
confidence: 85%
“…In vivo studies of efavirenz metabolism have largely reflected in vitro drug metabolism studies, which show that the primary route of efavirenz elimination is through CYP2B6-mediated hydroxylation (18)(19)(20). Of the genetically polymorphic CYPs evaluated in this study, only CYP2B6 metabolizer status was found to be a significant predictor of CL/F.…”
Section: Discussionmentioning
confidence: 85%
“…The potential contribution of efavirenz metabolites to CNS adverse drug reactions of efavirenz needs to be further examined [5]. The majority of efavirenz-induced CNS effects appear early, even after a single dose [6].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for the CNS toxicity of this drug are yet to be resolved. Efavirenz is metabolised by Cytochrome P450 enzymes and has a number of metabolites [2,[4][5][6]. There are two main metabolites of efavirenz, that is 7-and 8-hydroxefavirenz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Introduction : The major efavirenz metabolite, 8-hydroxy-efavirenz, has been reported as plausibly responsible for efavirenz-induced neurotoxic effects [13]. Notably, up to 35% of patients on efavirenz suffer from mood changes [4].…”
mentioning
confidence: 99%